2003
DOI: 10.1167/iovs.02-0824
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Activated Sialoadhesin-Positive Microglia during Retinal Degeneration

Abstract: During retinal degeneration, microglia are activated and express sialoadhesin. The temporal relationship between photoreceptor apoptosis and microglial response suggests that microglia are not responsible for the initial wave of photoreceptor death, and this is corroborated by the absence of iNOS and nitrotyrosine. Expression of sialoadhesin may indicate blood-retinal barrier breakdown, which has immune implications for subretinal gene therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 27 publications
5
55
0
1
Order By: Relevance
“…Moreover, infiltrating macrophages are thought to participate in the inflammation associated with retinal degeneration (56)(57)(58). Retinal macrophages Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, infiltrating macrophages are thought to participate in the inflammation associated with retinal degeneration (56)(57)(58). Retinal macrophages Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown recently that microglial migration and accumulation is enhanced in the degenerating retina such as in that of the RCS rat (Roque et al 1996), the rd1 (Zeiss and Johnson 2004;Andrieu-Soler et al 2005;Zeng et al 2005) or the rd2 mouse (Hughes et al 2003). Zeng and coworkers (Zeng et al 2005) have additionally shown in the rd1 retina that activated microglia express a multitude of signaling molecules (chemokines MCP-1, MCP-3, MIP-1α , MIP-1β, and RANTES) and microglia-derived toxic factor (TNF-α ) which may contribute to three different processes: 1 st , increased photoreceptor death due to the release of cytotoxic substances; 2 nd , recruitment of monocytes/macrophages to the site of injury through the release of chemokines and 3 rd , removal of cellular debris.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, retinal microglia are activated in response to nearly all pathological stages of the retina (Langmann, 2007), with microglial cells migrating to the layers affected by degeneration. Thus, the adult ONL which is normally devoid of microglial cells Santos et al, 2008;Bejarano-Escobar et al, 2011), is colonized by these cells in conditions of photoreceptor degeneration during normal development (Bejarano-Escobar et al, 2011) or under pathological or experimental conditions (Roque et al, 1996;Ng and Streilein, 2001;Harada et al, 2002;Hughes et al, 2003;Zeiss and Johnson, 2004;Zeng et al, 2005;Bailey et al, 2010;Santos et al, 2010).…”
Section: Microglia In the Experimental Tench Retinal Tissuementioning
confidence: 99%